A colisão de direitos fundamentais e a máxima da proporcionalidade - Vasconcellos, Helio Gualberto (2009)
This study was concerned with the phenomenon of collision of fundamental rights, and the current instrument of its solution. The research was focused on the precept of proportionality, whose bibliographic documents consulted, are trials of our courts and also the doctrine of national authors. The theoretical framework was build upon the thought of Robert Alexy, a constitutionalist who gave the most significant contribution in this issue. The title of this work is also a result of the theoretical framework. The human rights were discussed, including the motivation for the change of terminology to fundamental rights. The approach of fundamental rights converged in the collisions, generating the need of studying the instrument of its solution. The classical means of solutions were studied, and their insufficiency to solve the problems were appointed. About he ideal of proportionality, it was studied its origin and development. It was studied, in a particular way, the theory of Robert Alexy, who has, as already noted, intimate connection with the proportionality. The work that guided the researcher in this subject was "The Theory of Fundamental Rights", by Alexy. It has been explained his vision of the dogmatic, which we joined. It was also studied, the contribution of Alexy about the distinction between rules and principles, which is relevant to the topic. This led us to the innovative understanding of Alexy, about the principles as "warrants of optimization." We studied the means of solutions of the conflicts between rules and principles in collisions, as its "prima facie" character and a few others. It was also demonstrated the issue of rules and principles, as reasons. It was equally examined the character of the principles as fundamental rights, as showed by the relation principle x value. It was indicated the extention of the concept of principles, and examined the relationship of its theory with the precept of proportionality. Because of the confusion surrounding the doctrine of the precept of proportionality and reasonableness, we studied the identities and dissimilarities between them, calling the first, principle, for much of the doctrine, and thus also the last because of the majority of doctrine. About the inquiry (based on the doctrine), if they both are, the same precept, or,if each of them, are precepts with their own identity; we chose the last option and justified this choice. We reviewed the understanding of Brazilian jurisprudence on proportionality, concluding that our courts have applied this precept when it is necessary. Favorable to the precept is also the teaching of our doctrine. Given all these partial findings in favor, the conclusion we drew, which outlined the final of this research, could not fail to be for the needed of the precept - which, valued by the courts, should result in the recovery of jurisdiction itself.